Humility in Turkish University Student Athletes and Non-Athletes - Tingaz, Emre Ozan; Güvendi, Burcu (Asian Journal of Education and Training, 2019)
The main purpose of the current research is to examine the humility of university student athletes and non-athletes. In addition, it has been another focus of whether the humility differ according to gender, age, department and monthly expenditure. Furthermore, the humility of the athlete students according to their sports type, sports years and the best athletic scores was investigated. In the present study, two different public universities from Istanbul and Ankara, aged between 18, 23 (Mage = 20.49 years SD = 1.35), 54.3% (n = 222) were female and 45.7% (n = 187) were male, a total of four hundred nine athlete and non-athlete students were included through convenience sampling. The instrument selected for the study was the Humility Scale which has been developed by Elliott (2010) and adapted to Turkish by Sarıçam et al. (2012). The total score and sub-dimensions of humility in the present study did not differ significantly by gender, age, monthly expenditure, athletic status (athletes or non-athletes), sport type (team or individual sports) and sport year. On the other hand, in the sub-dimension of focus on others, it was found that the students in the primary teaching department had significantly higher scores than the physical education and sports teacher students. In modest self-assessment sub-scale, the average score of athletes who have the best athletic score in a Turkey competition higher than athletes who have the best athletic score in a regional competition.